Avillion Village Resort Online System / Zainorhuda Zainal Rashid - Zainorhuda, Zainal Rashid (2001)
Information Technology (IT) has a very significant influence in expanding organization’s capabilities particularly to meet the challenges from the borderless environment and global marketing capability. The IT needs in an organization therefore need to be identified that would have an edge and bigger influence in the creation of new culture of working, identify and creation of new business model. This Avillion Village Resort online system will be developed to provide an easy and convenience way for all users to gather information and doing online reservation. This system will allow users to access information just by clicking the mouse to have the best view complete information and online reservation of the hotel just from this website. Furthermore, this system will reduce time and provides the convenience of a paperless environment. Avillion Village Resort online system is a stand-alone and will be developed with the objectives of providing information for all the services of the resort and a complete form for user to do online reservation. Then, user will receive the confirmation letter, as their guarantee booking requires user credit card number or payment by cash as the deposit. There are two sections in this system where as user section and administrator section. The user section will be provided to any user to search their information about the hotel and can have a lot of convenience way to receive news updates exceptional offers and more and the administrator section is provided to user that registered as an administrator that will be in charge to maintain the data entry and upload the news of the hotel. This system also provides information about the specialty of the hotel with the best view images, travel agents services, FAQs and much more. It will be developed on the Windows 2000 Professional platform and utilizes Microsoft Access as the database to store the information. This system also will be used powerful tools for developing the web page contents, Dreamweaver 6.0 that offers more features than Microsoft FrontPage. In order to build a very user-friendly web page this system will be developed using scripting language technologies such as HTML, DHTML and also JavaScript. Using Microsoft Access to provide efficient and secure database to keep information of the clients will develop the online reservation and guarantee form. It is believed that the system will be created with proper environment to become the website that attract more people to reserve the room and increase the productivity of the resort. After all the development and implementation phases the system is running properly and can perform very well to the user after being tested in the testing stages. The system also needs a few enhancements to improve the performance of the system.